NMDA receptors are movin? in - NONG, Y (Current opinion in neurobiology, 2004)
Dynamic modulation of the number of postsynaptic glutamate receptors is considered one of the main mechanisms for altering the strength of excitatory synapses in the central nervous system (CNS). However, until recently N-methyl-d-aspartate (NMDA) receptors were considered relatively stable once in the plasma membrane, especially in comparison with alpha-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid (AMPA) receptors that are internalized at a high rate. A series of recent studies has changed this viewpoint by revealing that NMDA receptors are subject to constitutive as well as agonist-induced internalization through clathrin-mediated endocytosis. Surprisingly, agonist-induced internalization is not dependent on current flow through the NMDA channel, and the receptors are primed for this type of internalization by selective stimulation of the glycine site but not of the glutamate site. Endocytosis of NMDA receptors provides a fundamental mechanism for dynamic regulation of the number of NMDA receptors at synapses, which might be important for physiological and pathological functioning of the CNS.